PENGARUH KEBIASAAN BELAJAR DAN PENGGUNAAN MEDIA INFORMASI TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS X SMA N 1 TIGO NAGARI KABUPATEN PASAMAN - Siwat, Siwat; Ansofino, Ansofino; Ramayani, S.Pd,ME, Citra (Pendidikan Ekonomi, 2014)
ABSTRACTÂ Issues that are examined in this study is the influence of study habits and media usage information to the student learning outcomes of economic subjects in class X in SMAN 1 Tigo Nagari Pasaman. The purpose of this study was to analyze the influence of study habits and media usage information to the student learning outcomes of economic subjects in class X in SMAN 1 Tigo Nagari Pasaman. The technique of collecting data using questionnaires, the data were analyzed with multiple linear regression method. The results showed that the First: Study Habits positive and significant effect on student learning outcomes are indicated by a coefficient of 0.503 with a value of t_ test (count)> t_tabel ie 23.505> 1.984 and significant at 0.000 <Î± = 0.05. Second: Use of Media Information and no significant effect on student learning outcomes indicated by the t_ test (count) <t_tabel ie 0.795 <1.984 and significant at 0428> Î± = 0.05. Third: Study Habits and Use of Information Media jointly affect student learning outcomes indicated by the F-statistic values of 290 361 and f_ test (count)> f_tabel is 290.361> 3.91 with significant value of 0.000 <Î± = 0, 05 and the R-squared value of 0.814, which means 81.4% of student learning outcomes are influenced by variables study habits and media usage information while the rest is explained by other variables. Based on the research results, the researchers suggest to the school to continue to improve study habits and attention to students and that the school uses the media information that can improve student learning outcomes.